Utilization of Renewable and Waste Materials for Biodiesel Production as Catalyst - Prashant Kumar; Anil Kumar Sarma; M. K. Jha; Ajay Bansal; Bharvee Srivastava (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
The efficient and economic utilization of natural renewable and waste materials of various industries and biomass having non-homogeneous composition is a new dimension of research for biodiesel pro- duction. A combination of these renewable, waste materials and traditional heterogeneous catalyst can also be looked after for the possible solution of heterogeneous catalytic transesterification. This review discusses industrially derived and naturally occurring materials containing calcium, sodium, potassium etc, which were found instrumental for biodiesel production. About 60 research articles and patents have been reviewed and the findings are analysed in this article for developing industrial scale heterogeneous catalytic pilot plant facilities for biodiesel production. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).